Elaboração de perfil psicológico de autores de homicídios através da avaliação da cena do crime - Silveira, Leon Murelli (2013)
This work aims to bring the academic discussion about the Criminal Profiling to the brazilian reality. To start this debate here, what is understood today by Criminal Profiling is brought up. This is followed up by the historical evolution of the technique and similar attempts. This is paramount to its definition, distinguishing it from the others, as it is to its conscious implementation, which avoids repeating past mistakes. From there, the academic debate deepens with what exists of theoretical and empirical productions about the theme, which guides the majority of its current practice in England, under the directives of Investigative Psychology. The founded critiques about the theme are also brought up, which allows us to call the knowledge so produced as results of a discussion. The international knowledge is then contextualized to the national practice. For that, a juridical discussion is made of its implementation as an investigative technique, comprehending the experience of courts that have already dealt with the theme. Criminal Profiling have already arrived at Brazil. Though it has been utilized in investigations, there's a need for information on the theme in a national level which allows us to evaluate its applicability as proof, or even its effectiveness as an investigative tool. The Criminal Profiling needs the reliability and standardization that the scientific method offers to be more useful than harmful in Brazil. Reaching this conclusion, a proposition of a research is made at the end of this work with the intent of starting a line of study necessary to the implementation of the technique in the most efficient and safe way possible